Whole-Cell Vaccine Preparation Through Prussian Blue Nanoparticles-Elicited Immunogenic Cell Death and Loading in Gel Microneedles Patches - Wenxin Fu; Qianqian Li; Jingyi Sheng; Haoan Wu; Ming Ma; Yu Zhang (Gels)
Tumor whole-cell vaccines are designed to introduce a wide range of tumor-associated antigens into the body to counteract the immunosuppression caused by tumors. In cases of lymphoma of which the specific antigen is not yet determined, the tumor whole-cell vaccine offers distinct advantages. However, there is still a lack of research on an effective preparation method for the lymphoma whole-cell vaccine. To solve this challenge, we prepared a whole-cell vaccine derived from non-Hodgkin B-cell lymphoma (A20) via the photothermal effect mediated by Prussian blue nanoparticles (PBNPs). The immune activation effect of this vaccine against lymphoma was verified at the cellular level. The PBNPs-treated A20 cells underwent immunogenic cell death (ICD), causing the loss of their ability to form tumors while retaining their ability to trigger an immune response. A20 cells that experienced ICD were further ultrasonically crushed to prepare the A20 whole-cell vaccine with exposed antigens and enhanced immunogenicity. The A20 whole-cell vaccine was able to activate the dendritic cells (DCs) to present antigens to T cells and trigger specific immune responses against lymphoma. Whole-cell vaccines are primarily administered through direct injection, a method that often results in low delivery efficiency and poor patient compliance. Comparatively, the microneedle patch system provides intradermal delivery, offering enhanced lymphatic absorption and improved patient adherence due to its minimally invasive approach. Thus, we developed a porous microneedle patch system for whole-cell vaccine delivery using Gelatin Methacryloyl (GelMA) hydrogel and n-arm-poly(lactic-co-glycolic acid) (n-arm-PLGA). This whole-cell vaccine combined with porous gel microneedle patch delivery system has the potential to become a simple immunotherapy method with controllable production and represents a promising new direction for the treatment of lymphoma.